2005
DOI: 10.1113/jphysiol.2005.090639
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of potassium currents by angiotensin and oxidative stress in cardiac cells from the diabetic rat

Abstract: Diabetes induces oxidative stress and leads to attenuation of cardiac K + currents. We investigated the role of superoxide ions and angiotensin II (ANG II) in generating and linking oxidative stress to the modulation of K + currents under diabetic conditions. K + currents were measured using patch-clamp methods in ventricular myocytes from streptozotocin (STZ)-induced diabetic rats. Superoxide ion levels, indicating oxidative stress, were measured by fluorescent labelling with dihydroethidium (DHE). ANG II con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 62 publications
0
36
0
Order By: Relevance
“…Earlier work from our laboratory showed that cardiac angiotensin II levels and oxidative stress are increased in diabetic male hearts (41, 43). These changes are reduced or absent in diabetic females (41)(42)(43). Earlier work from our laboratory also showed that in vivo treatment of male rats with an angiotensin-converting enzyme (ACE) inhibitor reduces or prevents diabetes-induced increase in angiotensin II and the resulting oxidative stress (41).…”
Section: Gender Differences In Conductionmentioning
confidence: 69%
See 3 more Smart Citations
“…Earlier work from our laboratory showed that cardiac angiotensin II levels and oxidative stress are increased in diabetic male hearts (41, 43). These changes are reduced or absent in diabetic females (41)(42)(43). Earlier work from our laboratory also showed that in vivo treatment of male rats with an angiotensin-converting enzyme (ACE) inhibitor reduces or prevents diabetes-induced increase in angiotensin II and the resulting oxidative stress (41).…”
Section: Gender Differences In Conductionmentioning
confidence: 69%
“…Selective activation results in lower cellular angiotensin II levels in diabetic female hearts compared with diabetic male hearts (43). Concordantly, cells from diabetic females show less oxidative stress (41).…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…In streptozotocin-induced diabetes in rats, membrane K+ currents were attenuated secondary to increased angiotensin II-induced NADPH oxidase activation [47]. Angiotensin II-induced swelling-activated Cl− current in rabbit ventricular myocytes involved NADPH oxidase activation, and was inhibited by a range of inhibitors including gp91ds-tat [48].…”
Section: Effects Of Nadph Oxidase On Calcium Signalingmentioning
confidence: 93%